Beyond Leadership Titles: Director of Finance’s Accounting Expertise Outweighs President Director in Reducing Corporate Tax Avoidance - Satrio Dwi Aprian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines how the accounting educational background of the President Director and the Director of Finance influences corporate tax avoidance (TA) among consumer goods companies in Indonesia. Using a purposive sampling method, the study analyzes 176 firm-year observations from companies listed on the Indonesia Stock Exchange (IDX) during the 2017–2021 period. Data were analyzed using descriptive statistics and multiple linear regression with SPSS version 27. The results show that the accounting background of the President Director does not have a significant effect on corporate tax avoidance. In contrast, the accounting background of the Director of Finance has a negative and significant relationship with TA, indicating that accounting expertise among finance directors enhances tax compliance. These findings suggest that executives with accounting qualifications tend to support more transparent financial reporting and ethical tax management practices. Theoretically, this study contributes to the corporate governance and tax behavior literature by highlighting differences in executive roles. Practically, the findings suggest that accounting expertise should be considered in executive recruitment to promote responsible corporate tax practices.